INTENTION TO REPURCHASE INDRIVE AS ONLINE TRANSPORTATION: THE ROLE OF PERCEIVED EASE OF USE AND PRICE PERCEPTION (STUDY ON YOUNG PEOPLE IN MANADO) - Michael Yehudavid Jabbar; Paulus Kindangen; Emilia Gunawan (Universitas Sam Ratulangi, 2023)
The purpose of this research is to explore the roles of perceived ease of use and price perception on repurchase intention, study the case of customers of InDrive in Manado. This research is qualitative research using a case study approach. Primary data was gathered from a semi-structured interview of 13 informants that used InDrive at least once as the sample who were chosen using convenience sampling. The data was analyzed through qualitative data analysis. Narrative analysis was used to analyze the relationships in the research variables. The results show that relationship between perceived ease of use and price perception are partial and simultaneously gives positive impact on repurchase intention. However, the perceived ease of use has an indirect impact on repurchase intention meanwhile price perception has direct impact on repurchase intention. This research suggests that InDrive establish well-defined protocols and robust systems is important to address these concerns and ensure a safer and more reliable experience for users. Keywords: online transportation, perceived ease of use, price perception, repurchase intention, perceived usefulness, and security